2019
DOI: 10.3390/ijerph16214231
|View full text |Cite
|
Sign up to set email alerts
|

Public Knowledge about Dementia in China: A National WeChat-Based Survey

Abstract: Dementia is a serious public health problem. The more extensive dementia knowledge is, the more conducive it is to early prevention and treatment of dementia. However, no assessment of the general population’s dementia awareness has been conducted so far in China. Thus, this study assessed the national public knowledge of dementia based on mobile internet in China. We assessed 10,562 national respondents recruited based on the most popular social networking service in China, WeChat and analyzed the data using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
6
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 65 publications
5
31
6
3
Order By: Relevance
“…Previous studies suggested that the knowledge of the possibility that dementia could be prevented remained poor in general. A few studies conducted in China focused mainly on the recognition of prodromal symptoms of dementia [18,24]. The present results suggested that the overall understanding of factors associated with dementia among the Chinese population was more comprehensive than we initially believed based on similar studies in other countries [19,29,30].…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Previous studies suggested that the knowledge of the possibility that dementia could be prevented remained poor in general. A few studies conducted in China focused mainly on the recognition of prodromal symptoms of dementia [18,24]. The present results suggested that the overall understanding of factors associated with dementia among the Chinese population was more comprehensive than we initially believed based on similar studies in other countries [19,29,30].…”
Section: Discussionsupporting
confidence: 47%
“…However, insufficient awareness and knowledge of the potential of dementia prevention among the Chinese public has been a substantial obstacle for dementia control and management [23]. Some studies evaluated the Chinese population's overall understanding of dementia, suggesting that the recognition of dementia needed to be improved [24,25]. The awareness of specific protective and risk factors associated with dementia among the Chinese population is inadequate.…”
Section: Introductionmentioning
confidence: 99%
“…These ndings suggested the need to develop different approaches for different populations to disseminate knowledge about dementia. In the present study, no signi cant in uence of income or type of residence was found, which was contrary to previous ndings that people with low income or living in rural areas were less likely to understand that the risk of dementia could be reduced [24,37]. Future studies should recruit more individuals to con rm the results.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies suggested that knowledge of the possibility that dementia can be prevented remains poor in general. A few studies that were conducted in China mainly focused on the recognition of prodromal symptoms of dementia [20,26]. The present results suggest that the overall understanding of factors that are associated with dementia among the Chinese population is more comprehensive than we initially believed based on similar studies in other countries [21,28,29].…”
Section: Discussionmentioning
confidence: 46%
“…However, insufficient awareness and knowledge of the potential of dementia prevention among the Chinese public has been a substantial obstacle [25]. Some studies evaluated the Chinese population's overall understanding of dementia, suggesting that the recognition of dementia needs to be improved [26,27]. The awareness of specific protective and risk factors that are associated with dementia among the Chinese population is deficient.…”
Section: Introductionmentioning
confidence: 99%